PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI SEMANGAT KERJA KARYAWAN (Studi Kasus Pada Karyawan Bagian Produksi CV. Putra Jaya Sahitaguna, Semarang) - Yahyo, Yahyo; Waluyo, Handoyo Djoko; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
Employees represent the resource which play important role in supporting reaching of company efficacy. Therefore, company have to pay attention to the factors influencing employees in working. Good Motivation factor, good environment, appropriate compensation can grow the spirit of high job so that can affect the increase of performance of employees CV. Putra Jaya Sahitaguna, Semarang. This Research aim to know the motivation influence, environmental work, and compensation to employees performance of through spirit job. Sampel in this research is determined with the census approach many as 80 people. Its measurement scale use the scale likert. At data analysis use the simple linear regression test and test the doubled regresi. Research result show the motivate to have an effect on to employee morale of equal to 5,7 gratuity. Environmental work to have an effect on to employee morale of equal to 18,5 gratuity. Compensation have an effect on to employee moraleof equal to 10,4 gratuity.Motivate to have an effect on to employees performance of equal to 5,0 gratuity. Environmental work to have an effect on to employees performance of equal to 12,7 gratuity.Compensation have an effect on to employees performance of equal to 12,2 gratuity. Spirit of job have an effect on to employees performance of equal to 10,9 gratuity. Motivation, environmental work, and compensation to employee moraleof equal to 21,2. Motivation, environmental work the, compensation and employee morale to employees performance of equal to 20,3 gratuity. This research conclude that motivation, environmental work, and compensation have an effect on to employees performance. Companies need to approach the family, consider resting facilities, bathrooms, employee salaries and bonuses.